The Effectiveness of Buerger Allen Exercise and Hydrotherapy on Changes in Peripheral Blood Circulation and Neuropathic Pain Intensity in Preventing Diabetes Mellitus Complications in the Elderly - Yammar; Ratna Wardani; Joko Prasetyo; Asnuddin; Nirmawati Darwis; Ruslang (Journal Of Nursing Practice, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a major health problem in the elderly, often leading to complications, including impaired peripheral circulation, often accompanied by neuropathic pain. Therefore, foot activity therapy, including Buerger Allen exercises and hydrotherapy, is necessary to improve peripheral blood circulation. Purpose: This study aims to prevent complications of T2DM by improving peripheral blood circulation, as indicated by changes in Ankle Brachial Index(ABI) valuesand the intensity of neuropathic pain in the elderly. Methods: This quantitative study used a True Experimental Design with a pretest-posttest control group design. The study was divided into three groups: Buerger Allen exercise, hydrotherapy, and a control group. The sample consisted of 45 elderly individuals with type 2 diabetes mellitus (T2DM), selected using a simple random sampling method. This study was conducted in the Tempe District, Wajo Regency. Data analysis used a paired t-test to determine the effect of the three foot activity therapies. Data were analyzed using SPSS with a significance level of p < 0.05. Results: The study showed that the Buerger Allen exercises and hydrotherapy groups experienced significant changes in ABI valuesand neuropathic pain intensity before and after therapy (p-value 0.000). Meanwhile, the control group showed no significant changes in ABI values or neuropathic pain intensity from the pretest to the posttest (p-value  1.000). Conclusion: It can be concluded that the Buerger Allen exercises and hydrotherapy groups can improve peripheral blood circulation compared to the control group, thereby preventing complications associated with type 2 diabetes in the elderly.